Revisiting the labor demand curve: The wage effects of immigration and women’s entry into the US labor force, 1960–2010 - de Brauw, Alan; Russell, Joseph R. D (International Food Policy Research Institute, 2014)
The debate over the wage effects of immigration for native workers is an old one. One side of the debate claims that immigration has little if any negative impact on wages among natives, whereas others suggest that immigration has large, negative effects on native wages. On the latter side of the debate, many point to the work of Borjas (2003), who takes a national view of the US economy and estimates a wage elasticity of -0.4 with respect to immigration. In this paper, we replicate and update Borjas with the 2010 US census data, and use the method to study an even larger, concurrent labor supply shock, namely the entry of women into the labor force. We both find a much lower wage elasticity than Borjas to immigration (-0.2) and estimate a positive, statistically significant relationship between men’s wages and women’s entry into education-experience cells when wages are annualized. We take this evidence to suggest that the Borjas model is misspecified as it inadequately specifies substitution between immigrants and natives, and inadequately controls for structural change in the US economy.